An Analysis of Revenge in Ian Mc’Ewan’s Nutshell - Yuzirwan, M. Azel; Nasution, Siti Norma; Pratama, Diah Rahayu (Talenta Publisher, 2022)
The purpose of this study is to find out the main character’s revenge portrayed in the novel, the factors that causes revenge, and how the main character takes his revenge. This thesis uses revenge theories by Baron, Byrne, and Branscombe to analyze revenge as a form or behavior of act of someone repaying the actions of other in hopes of getting a better feeling. In completing the analysis, the writer used descriptive-qualitative research method by Miles and Huberman which represents all data in forms of words and sentences. Based on the analysis it can be found that this novel portraying the revenge by the main character stop them from escaping the city. The revenge in this novel carried out by the main character is very unusual and unexpected, yet very logic. Usually, people will try to hurt the other parties who hurt them, but in this novel, the main character go with different approach, by arriving to the world early than it supposed to be, resulting the mother and uncle failed to escape the police officer.